Toward a culturally sensitive conceptualization of resilience: Participatory research with war-affected communities in northern Uganda. (June 2015) - Vindevogel, Sofie; Ager, Alastair; Schiltz, Julie; Broekaert, Eric; Derluyn, Ilse
Resilience research with war-affected populations has long conceptualized resilience as the absence of psychopathology and operationalized it by use of standardized measures. However, literature on resilience increasingly highlights the importance of also including indicators of positively valued functioning as well as contextually sensitive indicators of resilience. This study used a participatory approach to examine the contextual conceptualization of youth resilience in the aftermath of war in northern Uganda, as defined by groups of stakeholders (youths, parents, elders, leaders, teachers) in four communities. The results identify 40 indicators covering a multiplicity of domains of functioning. The rationales behind these indicators were clustered into the broad themes: progress, self-reliance, social connectedness, morality, health, and comfort. The findings suggest that positively and negatively valued aspects of functioning are both key to conceptualizing resilience, and indicate the importance of including contextually distinguished indicators. The findings further point to the role of individual and collective processes in the construction of resilience, and to the need to take into account the contexts wherein resilience is conceptualized and observed. This study generated contextually sensitive indicators of young people's resilience, which can be used, complementary to existing measures of functioning, to provide a more comprehensive and culturally sensitive view of youths' resilience in the wake of war adversity.